2007
DOI: 10.1126/science.1131669
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscale Iron Enrichment Experiments 1993-2005: Synthesis and Future Directions

Abstract: Since the mid-1980s, our understanding of nutrient limitation of oceanic primary production has radically changed. Mesoscale iron addition experiments (FeAXs) have unequivocally shown that iron supply limits production in one-third of the world ocean, where surface macronutrient concentrations are perennially high. The findings of these 12 FeAXs also reveal that iron supply exerts controls on the dynamics of plankton blooms, which in turn affect the biogeochemical cycles of carbon, nitrogen, silicon, and sulfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
1,041
0
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,342 publications
(1,084 citation statements)
references
References 40 publications
37
1,041
0
6
Order By: Relevance
“…However, the SOFeX-South experiment revealed an increase of particle fluxes after fertilisation, which resulted in F Th of $ 1800 dpm m À 2 d À 1 at the MLD . The variability within the plankton community structure and different sampling time strategies among these experiments most likely played a crucial role in the variety of results obtained (Boyd et al, 2007;Buesseler et al, 2004).…”
Section: Results and Comparison With Other Studiesmentioning
confidence: 99%
“…However, the SOFeX-South experiment revealed an increase of particle fluxes after fertilisation, which resulted in F Th of $ 1800 dpm m À 2 d À 1 at the MLD . The variability within the plankton community structure and different sampling time strategies among these experiments most likely played a crucial role in the variety of results obtained (Boyd et al, 2007;Buesseler et al, 2004).…”
Section: Results and Comparison With Other Studiesmentioning
confidence: 99%
“…Over 30 years of research has demonstrated that Fe limitation controls the efficiency of the biological pump and the structure of phytoplankton communities in the SO (e.g., Martin, 1990;Coale et al, 2003;De Baar et al, 2005;Maldonado et al, 2005;Blain et al, 2007;Boyd et al, 2007;Smetacek et al, 2012). However, only the biologically active pool (defined here as bioavailable) is the fraction that can be effectively taken up by microorganisms to support their nutrient-dependent metabolic processes and growth (Hassler et al, 2012).…”
Section: Iron (Fe) Limitationmentioning
confidence: 99%
“…3.3.3.1 High Latitude HNLC Regions In certain regions that are known as high nutrientlow chlorophyll (HNLC) regions (Boyd et al 2007), some trace nutrients (notably iron) may remain low, even when other nutrients such as nitrogen, phosphorus and silica are available, limiting phytoplankton production. In HNLC regions in high latitudes (including parts of the Pacific and the Southern Ocean), the correlation between chlorophyll and SST may become weak or negative, indicating that phytoplankton growth is predominantly limited by nutrient availability rather than light availability.…”
Section: Regional Variationsmentioning
confidence: 99%